Inadequate shear bond strengths of self-etch, self-adhesive systems for secure orthodontic bonding - Isman, Eren; Karaarslan, Emine Sirin; Oksayan, Ridvan; Tuncdemir, Ali Riza; Usumez, Serdar; ADANIR, NEJDET; Cebe, Mehmet Ata (My University, 2012)
This study evaluated the shear bond strength (SBS) of a traditional orthodontic bracket bonding agent (Transbond XT) against two self-etch, self-adhesive systems (Maxcem Elite and Vertise Flow). Sixty premolar teeth and sixty brackets were randomly and equally divided into five groups: Transbond XT (TXT) as the control, Maxcem Elite (ME) without etching, ME with etching (ME/Etch), Vertise Flow (VF) without etching, and VF with etching (VF/Etch). Respective SBS results of the five groups were 9.86 +/- 3.20, 4.67 +/- 2.94, 7.82 +/- 2.56, 2.55 +/- 0.77, and 7.89 +/- 1.17 MPa. SBS values of the new self-etch adhesive systems were significantly lower than the traditional etch-and-rinse control (p0.005). After debonding, ARI scores -0- and -1- were predominant in non-etched ME and VF groups. It was concluded that new self-etch, self-adhesive bonding systems require additional phosphoric acid application to achieve comparable SBS values as the traditional orthodontic bonding agent.
Keywords: shear bond strength